Fraudulent Financial Reporting: Testing the Potential for Fraudulent Financial Reporting Using the Fraud Hexagon Theory (In Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2019-2021 Period) - Nurbaiti, Annisa; Taqia, Azzahra Luciana (UNIVERSITAS PAKUAN, 2024)
Fraud in financial reporting can occur either due to intentional actions or negligence, resulting in financial reporting that does not follow generally accepted accounting principles. When these differences and omissions are significant, they can have a serious impact on the decisions chosen by interested parties. The study is useful in order to understand how various factors in the fraud hexagon, namely pressure, ability, opportunity, rationalization, arrogance, and collusion, can influence the occurrence of fraud in financial reporting. The study was conducted at manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The research method adopted a quantitative approach and collected data through a purposive sampling technique using secondary data in the form of annual financial reports from manufacturing companies. The study involved 180 data observations obtained from 61 different companies. In order to analyze the data, the study used logistic regression analysis with the help of SPSS 24 software. The results of the study showed that the pressure factor had a positive impact on financial reporting fraud. However, other factors such as capability, opportunity, rationalization, arrogance and collusion have no effect on fraud in the financial statements of manufacturing companies listed on the IDX throughout the period 2019-2021. For subsequent researchers, it is recommended to increase and expand other variables and objects other than manufacturing companies listed on the Indonesia Stock Exchange.